A Study on internal conflict in developing countries causes and way outs - Upadhyaya, Buddhi Prasad (KDI School, 2011)
Policy and conflict are interrelated and shapes each other. Conflict has been shifted from global level to national level as internal conflict after the end of Second World War. However, such internal conflict is also a major source of terrorism and harms in global level. So, managing conflict is equally important for socio-economic development of country domestically as well as protecting the world from terrorism. Various studies and researches have been carried out in national and international level for identifying the root causes of internal conflict. However, it is difficult to agree on common causes of such conflict because of the difference in country specific context and situation that may shape conflict differently. Most of studies have focused on the diversity as a main cause of conflict and poverty, inequality and other poor availability of basic needs as also byproduct of such diversity because of the difficulty in agreeing for public goods in such society. Some studies focusing the case of Nepal has explored the poverty, inequality, availability of forest area as supporting factors of conflict. As a student of public policy, I perceived conflict differently linking with policy perspective. In spite of various researches carried out in different level, the root cause of conflict still remained unidentified and effective measures for conflict resolution could not work well in most cases. In this background, I have conducted this study mainly to identify main causes of internal conflict and way out, focusing on the decade long armed conflict in Nepal with some cross country comparison. I analyzed any internal conflict as a disturbance in the normal social and national system because of the result of weak management of differences and diversity in society. Differences and diversity are natural in human society. We need to have effective policy measures to harmonize and coordinate differences to manage from family level to national as well as international level. A decade (from 1996 to 2006) long armed conflict in Nepal left 785 people disabled, 1006 people disappeared and 13,236 people killed. The destruction of social capital (trust and believe), physical infrastructure and pooling back the development process cannot be measured in monetary term. However, it has provided an opportunity of fresh start in socio-economic transformation. Regarding the causes of the conflict in Nepal, mainly the following factors contributed the most based on my analysis: a) Increased aspirations of people remained unaddressed (gap between expectation and achievement) b) Presence of ambitious political ideology for overall state restructuring through the strategy of armed/guerrilla war c) Proper match of these two situations d) Absent of effective institutional mechanism for interest based negotiation process e) Absent of Zone of Possible Agreement (ZOPA) at the initial negotiation f) Fragile political situation and poor governance during the negotiation process g) Discrimination among different regions by the state. For example, the mid-western and far-western regions were left behind from the state mainstream h) Discrimination among the citizen in basic services as well as opportunities from the state functioning (employment in Nepal police, school teacher and state owned enterprises) i) Power seeking and worshipping culture of society hindering effective policy management All these factors are related to policy management. Effective policy in these issues could contribute for managing and transforming the conflict in time. But, due to the absent of coherent and coordinated policy management, nearly 15 thousand people became direct victim and the country went back in socio-economic development. It can be linked with the coherent and harmonized policy mainly in the following perspective: i. Political, economic, and social sector ii. From structure of government (macro level) to the operational level iii. From people's aspiration to the real implementation iv. Balancing immediate, short term and long term policies v. Regional balance in development vi. Coordination among all from formulation to implementation In case of Nepal, we missed these parts from the state functioning and created some favorable situation for armed conflict. Furthermore, the power seeking and worshipping culture of Nepalese society and could not systematize the governance in operational level. Poor policy management in these areas created the conflict in Nepal as well as elsewhere. Any Struggle in the world takes place for better life through equality and equity in the social system. Internal conflict in international arena is also result of policy gap or weak policy management. Country situation matters in cause of conflict. What types of policy to be adopted depends on the natural justice as well as socio-cultural setup. South Africa, Singapore and Switzerland managed conflict through inclusive policy and system. In South Africa, the policy prohibiting blacks from access to power exercise and other key opportunities caused conflict and the abolition of all discriminatory laws and establishment of inclusive political, economic and social policy and institutional setups transformed the conflict in socio-economic development. Similarly, the well integration of socio-cultural diversity in Singapore created better opportunity for socio-economic development by achieving synergic result through integration. The diversity has been the beauty of society because of the higher benefit from comparative and competitive advantages justified by the globalized world. So, assurance for equality among the different regions and among the citizen of the country with some special care or protection for marginalized and disadvantaged area and group for equal footing is essential for managing and transforming conflict. This can be assured through the effective policy management from macro level to the micro/operational level in different dimensions of human life including political, economic, social and etcetera by coherent and coordinated way of all policy cycle with assurance of effective implementation. Absent of such situation may create conflict. The forms and level of conflict may depend on the availability of leading ideology and its strategy as well as the level of discrimination in state behavior. So, reducing the policy gap between the aspiration of people and the state behavior reduces the conflict in any area. Interest and position matter in conflict management. Absent of ZOPA at the initial phase of negotiation was transformed to the successful end of conflict through refining interest and strengthening position with some strategic intervention. The level of public support on Maoist agenda increased from the weak governance and coalition with parliamentary parties with some adjustment in agendas. The coalition between two political powers by harmonizing their interest each other converted the armed conflict into joint people's movement and achieved republic country and also constituent assembly by strengthening own position and weakening the king's position. Finally, refining the overall policies and system through state restructuring from macro level to micro level has brought all Nepalese people towards the transformation of conflict toward the socio-economic development. So, policy matters for occurrence as well as curing the conflict and also a means of socio-economic transformation. From the study, my recommendations are: 1. Differences and diversity should be recognized, accepted and managed by taking account of country specific background. 2. Assuring the feeling of fairness is foundation of human life and policy and state behavior are means for this. 3. Policy is main instrument for managing country. So, we need to minimize the gap between people's aspiration and policy agenda, agenda and policy approval, policy approval and its implementation and improving from feedback in political, economic and socio-culture areas. 4. Defective policy creates conflict and again need to have another policy. So, we need to be sincere while adopting any policy and should assess the short term as well as long term perspective and consequences of the policy. 5. Taking the case of Nepal, unfair state behavior among different territory of the country and unfair behavior among people from different level of political and economic approach made the conflict success. So, decentralized state mechanism and equal behavior among all corner of the country and all people should be assured. In addition, the backward area and marginalized people should have special care and priority from the state behavior for compensating the past unjust. 6. Diverse language, religion, culture should be respected and proper opportunity should be provided for development of each. 7. Vertical and horizontal coherence and coordination should be assured in policy formulation and implementation 8. Provision of policy creates aspiration and expectation but poor implementation makes frustration. So, only implementable policy should be adopted. 9. An inbuilt institutional mechanism should be established from the central to local level to manage conflict effectively with some conflict transformation process. So, policy and conflict are interrelated and shapes each other. Defective policy creates conflict and effective policies manage it. However, the form and modality of conflict depends up on the availability of leading ideology as well as its strategies and also the level of unjust behavior from the state. Furthermore, coordination and coherence between different policies in different level of government through the whole policy cycle is crucial for transforming conflict with constructive achievement.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Nepal.